Correlation of expression of Cyclin D1 and E-cadherin with gleason grade, serum prostate specific antigen levels and prostatic volume in prostatic carcinoma - Aatirah, C; Bhatia, Jasvinder Kaur; Sandhu, JS; Bhatia, Ravjot Singh (Journal of Pathology of Nepal, 2023)
Background: Prostate cancer is increasingly being diagnosed early due to easy access and availability of better diagnostic modalities. Gleason scoring is important for prognosis and is used to determine the management protocol. As the behavior of these tumors is unpredictable, many markers are being investigated. Cyclin D1 and E-Cadherin have been linked to the development, progression, and aggressiveness in some studies. We studied the expression of E cadherin and cyclin D1 in various grades to understand their relationship with clinicopathologic features, PSA, and prostatic volume. Material & methods: 52 patients diagnosed with prostatic adenocarcinoma on core biopsy after ethical clearance in our tertiary care center were included in the study and their records were retrieved. Hematoxylin and Eosin stained sections were used for Gleason scoring as well as Gleason grade group as per existing protocols. Immunohistochemistry using antibodies against Cyclin D1 and E-Cadherin along with appropriate controls was performed. Studied parameters were correlated with E-Cadherin and cyclin D1. We used a statistical software package (version 22, IBM, US). Results: Cyclin D1 showed increasing immunoexpression with an increase in Gleason score and Gleason grade group emphasizing a significant correlation between these parameters (p= 0.001). There was a significant negative association between E-cadherin score, Gleason score, and Gleason grade group (p=0.001). No correlation was obtained with serum PSA or prostatic volume. Conclusions: E-cadherin and Cyclin D1 dysregulation could be used as prognostic and predictive markers in prostatic carcinoma.